2018
DOI: 10.1111/hae.13463
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI deficiency is not associated with an increased risk of pneumonia and pneumonia‐related mortality

Abstract: FXI deficiency was not associated with an increased risk of pneumonia, pneumonia severity or short-term mortality among patients with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The discovery that FXI knockout mice display an exaggerated pulmonary inflammatory response to inhaled dust mites, and that these mice have worse overall survival upon exposure to Streptococcus pneumoniae and Klebsiella pneumoniae compared to wild‐type animals, raised concerns that FXI inhibition may have unintended consequences in certain infectious contexts. In evaluating these concerns, Salomon et al found that people with partial and complete FXI deficiency did not experience a significantly higher incidence of pneumonia, severe pneumonia, or short‐term mortality compared to those with normal FXI activity. This indicates that the physiologic role of FXI in humans may differ from that in certain other mammal species.…”
Section: Limitations and Remaining Questionsmentioning
confidence: 99%
“…The discovery that FXI knockout mice display an exaggerated pulmonary inflammatory response to inhaled dust mites, and that these mice have worse overall survival upon exposure to Streptococcus pneumoniae and Klebsiella pneumoniae compared to wild‐type animals, raised concerns that FXI inhibition may have unintended consequences in certain infectious contexts. In evaluating these concerns, Salomon et al found that people with partial and complete FXI deficiency did not experience a significantly higher incidence of pneumonia, severe pneumonia, or short‐term mortality compared to those with normal FXI activity. This indicates that the physiologic role of FXI in humans may differ from that in certain other mammal species.…”
Section: Limitations and Remaining Questionsmentioning
confidence: 99%
“…FXI serves a modest role in haemostasis, and the hope is that drugs that inhibit FXIa, or that lower the plasma concentration of FXI, will prevent thrombosis while having a smaller impact on haemostasis than currently used anticoagulants. In this issue of Haemophilia , Salomon and colleagues report that FXI deficiency in humans does not influence the incidence or severity of community‐acquired pneumonia . To appreciate the importance of this study, we must consider what is known about FXI in the pathogenesis of infection in general, and to injury in the lungs in particular.…”
mentioning
confidence: 99%
“…The implications of the mouse studies for human pathology are far from clear, but they raise a concern that therapies targeting FXI/FXIa may increase the risk and/or severity of lung infections in humans. The study from Salomon et al addresses this concern . They identified individuals from a large medical practice in Israel who underwent evaluation for FXI deficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic studies of humans with FXI deficiency reported identical rates of hospitalization for pneumonia and pneumonia‐related outcomes as controls with normal FXI levels. To our knowledge, there are no reports linking human FXI deficiency with an immunocompromised phenotype 24 . Thus, while contact activation appears to contribute to proinflammatory and procoagulant pathways in humans, the absence of FXI does not seem to significantly compromise host defense or hemostasis.…”
Section: Human and Animal Data Suggesting The Potential Safety Of Conmentioning
confidence: 88%